On a convex combination of Lotka–Volterra operators - Mukhamedov, Farrukh; Pah, Chin Hee; Rosli, Azizi (Elsevier B.V., 2024)
We consider a convex combination of two classes of Lotka–Volterra operators defined on 2-dimensional simplex. Earlier, the dynamics of a particular case of the considered operators has been investigated. However, its bijective property was not studied. In this paper, we are able to establish that such maps are homeomorphism of the simplex.